Preparation method of aluminum electrolytic capacitor special for low-temperature-resistant detonator trigger
By optimizing the structure and preparation process of aluminum electrolytic capacitors, the problem of tantalum capacitors being prone to explosion and ignition in high and low temperature environments is solved, and the high capacitance, low leakage current and wide working temperature range of aluminum electrolytic capacitors are achieved, which is suitable for detonator detonators.
Patent Information
- Application Number
- CN202411829437.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Existing tantalum electrolytic capacitors are prone to explosion and ignite in high and low temperature environments, and have limited resources and high processing costs, making it difficult to meet the safety and economic requirements of detonator detonators for capacitors.
By optimizing the structure and preparation process of aluminum electrolytic capacitors, high-purity aluminum foil is processed using specific pore and hole reaming processes, and combining specific electrolytic paper and electrolyte formulations, low-temperature resistant aluminum electrolytic capacitors are prepared.
实现了铝电解电容的高电容量、低漏电流和宽工作温度范围,体积小、成本低,能够替代钽电容在雷管引爆器中的应用。
Smart Images

Figure BDA0005185209600000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum electrolytic capacitors, and in particular relates to a method for preparing a special aluminum electrolytic capacitor for a low-temperature resistant detonator initiator. Background Art
[0002] At present, the continuous development and improvement of electronic detonator technology has posed a technical threat to electric and non-electric detonators. Electronic detonators achieve high-precision detonation timing control, providing new technical support for precise blasting design, blasting effect control, blasting mechanism and process simulation research. Its technical superiority has been increasingly recognized in the global blasting industry, especially as the production cost of new electronic detonators continues to decline. Its production and application has expanded from the early rare and precious mineral mining field to ordinary mines and quarries, high-speed railways and highway tunnels.
[0003] The current common concern of electronic detonator users is still safety. The safety of the electronic detonator itself is mainly determined by its ignition delay circuit. The charging transistor and the discharging transistor form the main ignition circuit of the system. The electrolytic capacitor is discharged through the ignition transistor under the control of the microcontroller to ignite the ignition head.
[0004] Tantalum electrolytic capacitors are currently used. The characteristics of tantalum electrolytic capacitors are small size, long life, high and low temperature resistance, and excellent filtering performance. At the same time, tantalum has a high melting point, and its parameter performance is not easily affected by the external temperature. However, tantalum capacitors will explode and catch fire after the ripple current exceeds the rated value, and tantalum capacitors have poor overcurrent resistance and are very easy to catch fire. Tantalum metal is a non-renewable mineral resource, and the global tantalum ore content is very limited. In addition, because tantalum is resistant to high temperatures and corrosion, the processing cost is relatively high, resulting in high prices for tantalum capacitors.
[0005] Therefore, it is necessary to develop an aluminum electrolytic capacitor specially designed for low-temperature resistant detonator detonators. Not only is the production process simple, the materials are common, and the price is cheap, but the prepared aluminum electrolytic capacitor has excellent electrical properties, a wide operating temperature range, and a small size. It can replace tantalum capacitors in detonator detonators. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a special aluminum electrolytic capacitor for a low-temperature resistant detonator detonator, which improves the electrical performance and operating temperature range of the capacitor by optimizing the structure of the capacitor and the preparation process of each component, while having a small volume and low cost.
[0007] A method for preparing an aluminum electrolytic capacitor specially used for a low-temperature resistant detonator detonator comprises the following steps: cutting positive electrode foil and negative electrode foil and riveting them with a positive guide pin and a negative guide pin; placing electrolytic paper between the riveted positive electrode foil and negative electrode foil and winding them to form a core package, injecting electrolyte into the core package, and sealing it in an aluminum shell with colloid particles to obtain a semi-finished capacitor; washing the semi-finished capacitor, sleeve-fitting it, and sequentially performing primary aging selection, secondary aging selection, observing the appearance, and inspecting it to obtain the capacitor.
[0008] The preparation method of the positive electrode foil comprises the following steps: taking a high-purity aluminum foil for pretreatment, performing a pore-forming and pore-expanding treatment, and air-drying to obtain the positive electrode foil.
[0009] The specific steps of the pretreatment are: immersing the high-purity aluminum foil in the immersion liquid for 10 to 20 seconds, then taking it out and air-drying it.
[0010] Preferably, the impregnation liquid is an aqueous solution of acrylic resin.
[0011] Preferably, the mass fraction of acrylic resin in the acrylic resin aqueous solution is 0.5% to 2%.
[0012] Preferably, the acrylic resin has a solid content of 39% to 41% by weight and a viscosity of less than 200 cps.
[0013] In some preferred embodiments, the water-based acrylic resin is purchased from Guangdong Xidun New Material Technology.
[0014] The specific steps of the pore generation are: the impregnated aluminum foil is used as an anode and the graphite is used as a cathode, and is placed in a pore generation solution at a temperature of 80 to 90° C. and a current density of 0.1 to 0.2 A / cm 2 The pore-forming treatment was carried out for 2 to 3 minutes under the conditions. After completion, the aluminum foil was rinsed with deionized water and air-dried.
[0015] Preferably, the pore-forming solution is a mixed acid and metal ion aqueous solution.
[0016] Preferably, the concentration of the mixed acid in the pore-forming solution is 5-7 mol / L.
[0017] Preferably, the mixed acid is sulfuric acid and hydrochloric acid in a molar ratio of (3-5):1.
[0018] Preferably, the content of metal ions in the pore-forming solution is 50-150 ppm.
[0019] Preferably, the metal ions include one or more of ferric ions, ferrous ions, cupric ions, and zinc ions.
[0020] The specific steps of the hole expansion are: the aluminum foil with holes is used as an anode and the graphite is used as a cathode, and they are placed in a hole expansion solution at a temperature of 80 to 90° C. and a current density of 0.1 to 0.2 A / cm 2 The hole expansion treatment was carried out for 4 to 8 minutes under the conditions. After the treatment, the aluminum foil was rinsed with deionized water and air-dried.
[0021] Preferably, the pore-expanding solution is an aqueous hydrochloric acid solution.
[0022] Preferably, the concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 0.8 to 1.2 mol / L.
[0023] The inventors found that the specific volume of the positive electrode foil can be increased by using a specific method to process the high-purity aluminum foil to obtain the positive electrode foil, thereby increasing the capacitance of the capacitor and reducing the leakage current. This may be because through the specific pore-forming and pore-expanding process, on the one hand, the mixed acid system of sulfuric acid and hydrochloric acid in the pore-forming solution, and the metal ions of a specific concentration act together on the surface of the aluminum foil to form initial corrosion holes, sulfuric acid provides hydrogen ions to promote corrosion, and the chloride ions in the hydrochloric acid have a depassivation effect, which accelerates the formation of pitting corrosion. The addition of metal ions can occupy the corrosion sites of Cl- to a certain extent, reduce the useless corrosion of Cl-, improve the corrosion morphology of the aluminum foil, and further refine the corrosion hole structure. At the same time, it helps the discharge of Al3+ in the tunnel hole, so that the tunnel hole continues to grow and improves the uniformity of the hole distribution. On the other hand, the pore-expanding treatment makes the initial corrosion holes further expand and interconnect to form a more complex tunnel hole structure. This structure greatly increases the specific surface area of the aluminum foil, provides more charge storage space for the capacitor, thereby increasing the capacitance of the capacitor, and the corrosion holes with uniform distribution and moderate depth help reduce the generation of leakage current.
[0024] Preferably, the negative electrode foil is a high-purity copper foil.
[0025] Compounding the positive electrode foil prepared by the present invention with a high-purity negative electrode foil can comprehensively improve the composite specific capacity, so that devices with the same energy density can be made smaller, which is suitable for application in electronic detonator detonators.
[0026] The positive guide needle and the negative guide needle are tinned copper clad steel wires (CP wires).
[0027] The number of layers of the electrolytic paper is 1.
[0028] The conditions for the primary aging selection are: constant current and constant voltage are used, a constant current of 60 to 70 μA is applied, and after the voltage reaches 440 to 460 V, constant voltage aging is performed for 2 to 6 hours. After the primary aging, the leakage current is tested, and if ≤40 μA, it is qualified and proceeds to the next step.
[0029] The conditions for the secondary aging selection are: pulse and constant voltage methods are used, charging for 120s and discharging for 10s is one pulse, aging for 1-2h at a voltage of 440-460V, and testing the leakage current after secondary aging. If ≤40μA, it is qualified and proceeds to the next step.
[0030] The inventors found that the use of two different steps of aging selection can ensure that the final screened capacitors have high stability, low leakage current, and reliable quality. This may be because on the one hand, the primary selection uses constant current and constant voltage aging, which can not only preliminarily screen out capacitors with potential leakage or short circuit problems, or capacitors that cannot withstand high voltage, but also help activate the self-repair mechanism inside the capacitor and reduce leakage; on the other hand, the secondary selection uses pulse and constant voltage aging, which not only tests the charging and discharging performance of the capacitor, but also can accelerate the aging process inside the capacitor to a certain extent, thereby exposing potential performance problems more quickly. At the same time, it also helps to further activate the self-repair mechanism inside the capacitor and reduce leakage. The combination of the two aging methods can repair and solidify the aluminum oxide destroyed in the manufacturing process and improve its parameters, insulation properties, etc.; at the same time, abnormal quality products are eliminated during testing.
[0031] The preparation method of electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 85-90°SR, and diluting it with first deionized water to obtain liquid one; taking modified cellulose fiber, mixing it in second deionized water, dispersing it, adding it to liquid one, homogenizing it for 2-4 hours, making wet paper, pressing and drying the wet paper, and calendering it to obtain electrolytic paper.
[0032] Preferably, the average fiber length of the bleached kraft softwood pulp is 2.8 to 3.2 mm, the average fiber roughness is 18 to 20 mg / 100 g, and the average fiber content is (2.8 to 3.0)×10 6 roots / g, and a viscosity of 18 to 22 CP; further preferably, the average fiber length of the bleached kraft softwood pulp is 3.1 mm, the average fiber roughness is 20 mg / 100 g, and the average fiber content is 2.9×10 6 roots / g, viscosity is 20CP.
[0033] In some preferred embodiments, the bleached kraft softwood pulp is purchased from Canada Goodsound 100.
[0034] The inventors have found that the use of specific bleached sulfate softwood pulp as a raw material to prepare electrolytic paper can reduce the internal resistance of the capacitor while also improving its low temperature resistance. This may be because the use of bleached sulfate softwood pulp with longer fibers and lower average fiber content as the raw material for electrolytic paper, combined with a specific pressing pressure, can prepare electrolytic paper with lower density and developed pores, which not only helps the flow of electrolyte and the transmission of ions, thereby reducing the internal resistance of the capacitor, but also when the fluidity of the electrolyte decreases at low temperatures, the specific pore structure of the electrolytic paper can also help maintain the fluidity of the electrolyte, thereby improving the low temperature resistance of the capacitor. In addition, by controlling the thickness of the electrolytic paper, it can avoid affecting the insulation and thus the leakage current while transmitting ions. However, at extreme temperatures, the structure of the electrolytic paper is not very stable, affecting the performance of the capacitor.
[0035] Preferably, the mass concentration of the absolute dry pulp in the liquid 1 is 1.5 to 2.5 g / L.
[0036] Preferably, the added amount of the modified cellulose fiber is 1% to 3% of the mass of the absolute dry pulp.
[0037] Preferably, the mass ratio of the modified cellulose fiber to the second deionized water is 1:(100-200); further preferably, it is 1:150.
[0038] The preparation method of the modified cellulose fiber comprises the following steps: uniformly dispersing the cellulose fiber in a third deionized water, adding a modifier, adjusting the pH of the system to be stable between 10 and 10.5, reacting for 3 to 5 hours, washing the product with deionized water until it is neutral, and drying the product.
[0039] Preferably, the cellulose fibers include first cellulose fibers and second cellulose fibers.
[0040] Preferably, the first cellulose fibers have a length of 0.1 to 1 nm and a diameter of 100 to 1000 nm.
[0041] Preferably, the second cellulose fibers have a length of 1 to 20 μm and a diameter of 20 to 80 nm.
[0042] In some preferred embodiments, the first cellulose fiber and the second cellulose fiber are both purchased from MFC and CNF-H1 produced by Zhejiang Jinjiahao Green Nanomaterials Co., Ltd.
[0043] Preferably, the mass ratio of the first cellulose fiber to the second cellulose fiber is (2-4):1; more preferably, it is 3:1.
[0044] Preferably, the mass ratio of the cellulose fiber to the third deionized water is 1:(150-250); further preferably, it is 1:200.
[0045] Preferably, the modifier is 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite.
[0046] Preferably, the mass ratio of the 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite is 1:(4-6):(290-310); further preferably, it is 1:10:300.
[0047] Preferably, the amount of the modifier added is 5 to 8 times the mass of the cellulose fiber.
[0048] Preferably, the wet paper making weight is 24-28 g / m 2 .
[0049] Preferably, the calendering treatment conditions are: temperature 62-66°C, pressure 0.15-0.2 kgf / cm 2 .
[0050] Preferably, the thickness of the electrolytic paper is 35-45 μm.
[0051] The inventors found that adding two different cellulose fibers to a specific bleached kraft softwood pulp and modifying it at the same time can reduce the internal resistance of the capacitor while improving the stability of the capacitor at high and low temperatures. This may be because the introduction of two cellulose fibers with different aspect ratios from the fibers of bleached kraft softwood pulp can increase the complexity and diversity of the fiber structure inside the electrolytic paper. The long fibers can provide a good conductive channel to promote the rapid transmission of charge inside the electrolytic paper; the short fibers can fill the gaps between the long fibers to form a tighter fiber network, thereby improving the density and strength of the electrolytic paper. The synergistic effect of the long and short fibers enables the electrolytic paper to have good stability and durability while maintaining a high capacity. During the mixing process, the fibers of the bleached kraft softwood pulp and the two cellulose fibers with different aspect ratios will interact with each other, which helps to enhance the bonding force between the fibers, so that the electrolytic paper is not easily deformed or broken when subjected to temperature changes, thereby maintaining stable capacitance performance. By modifying the cellulose fibers, not only can the dispersibility of the cellulose fibers in the bleached kraft softwood pulp be improved, thereby further improving the stability of the electrolytic paper, but also the absorption and retention capacity of the electrolytic paper for the electrolyte can be improved, further improving the capacitance performance.
[0052] In some preferred schemes, the combination of high-conductivity CP wire guide needles and low-density electrolytic paper can reduce the equivalent series resistance of the capacitor. This is because the combination of the two has a synergistic effect. The high-conductivity CP wire guide needle is responsible for efficiently transmitting current, reducing resistance thermal effects and energy losses; while the low-density electrolytic paper provides good insulation performance, protecting the circuit from external interference and damage. The two cooperate with each other to jointly improve the overall performance of the capacitor. At the same time, because the high-conductivity CP wire guide needle reduces the resistance during current transmission, and the low-density electrolytic paper reduces the dielectric loss and insulation resistance thermal effects of the capacitor, the two work together to significantly reduce the ESR value of the capacitor, thereby improving the stability of the capacitor.
[0053] Preferably, the electrolyte comprises lithium bis(trifluoromethanesulfonyl imide) and an organic solvent.
[0054] Preferably, the concentration of the lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 0.5 to 1.5 mol / L.
[0055] Preferably, the organic solvent is γ-butyrolactone, ethylene carbonate, propylene carbonate, or methyl acetate.
[0056] Preferably, the volume fraction of γ-butyrolactone in the organic solvent is 50% to 60%.
[0057] Preferably, the volume ratio of ethylene carbonate, propylene carbonate and methyl acetate is 1:(1-3):(0.5-2); more preferably, it is 1:2:1.
[0058] The inventor found that the electrolyte can be prepared by selecting a specific organic solvent and a lithium salt, and can improve the high temperature resistance and low temperature resistance of the capacitor, widen the operating temperature range, and can also improve the capacitance. The γ-butyrolactone solution has high stability, and the chemical structure is stable at high and low temperatures, but its conductivity is low. The present invention is through the synergistic effect between four kinds of organic solvents, on the one hand, there is good mutual solubility and synergistic effect between ethylene carbonate and propylene carbonate, the addition of ethylene carbonate can reduce the melting point of propylene carbonate, improve the low temperature performance of the electrolyte, and at the same time, the mixing of the two can form a stable solvation structure, which helps the transmission and storage of ions, and on the other hand, methyl acetate can greatly improve the problem of low conductivity of pure γ-butyrolactone in the γ-butyrolactone solvent system, reduce the internal resistance of the capacitor, and also retain the advantages of good stability and high voltage resistance of γ-butyrolactone, reduce the decomposition of electrolyte and corrosion of electrodes, thereby reduce leakage current. However, due to the relatively poor high temperature resistance and low temperature resistance of methyl acetate, its addition amount needs to be controlled.
[0059] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0060] 1. The present invention provides a method for preparing a low-temperature resistant aluminum electrolytic capacitor specially used for detonator detonators. The production process is simple, the materials are common, and the price is cheap. The prepared aluminum electrolytic capacitor has excellent electrical properties, a wide operating temperature range, and a small size, and can be applied to detonator detonators.
[0061] 2. The present invention uses a specific method to process high-purity aluminum foil to obtain positive electrode foil, which can increase the specific capacity of the positive electrode foil, thereby increasing the capacitance of the capacitor and reducing leakage current; at the same time, the positive electrode foil prepared by the present invention is compounded with a high-purity negative electrode foil, which can comprehensively improve the composite specific capacity, so that devices with the same energy density can be made smaller, which is suitable for application in electronic detonator detonators.
[0062] 3. The present invention uses two different steps of aging screening, which can ensure that the capacitors finally screened out have high stability, low leakage current and reliable quality.
[0063] 4. The present invention adopts high conductivity CP wire guide needle and low density electrolytic paper to reduce the ESR value of the product.
[0064] 5. The present invention uses specific organic solvents and lithium salts to prepare the electrolyte, which can improve the high temperature resistance and low temperature resistance of the capacitor, widen the operating temperature range, and also increase the capacitance.
[0065] 6. The present invention adopts high-purity guide needles and aluminum stems for pressure chemical processing to ensure the stability of product parameter performance. DETAILED DESCRIPTION
[0066] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0067] The raw materials used in the present invention are all commercially available, specifically:
[0068] The acrylic resin has a solid content of 39% to 41% by weight and a viscosity of less than 200 cps and is purchased from Guangdong Xidun New Materials Technology.
[0069] The average fiber length of bleached kraft softwood pulp is 3.1 mm, the average fiber roughness is 20 mg / 100 g, and the average fiber content is 2.9 × 10 6 roots / g, viscosity is 20CP, purchased from Canada Good Sound 100.
[0070] The length of the first cellulose fiber is 0.1-1 nm, and the diameter is 100-1000 nm; the length of the second cellulose fiber is 1-20 μm, and the diameter is 20-80 nm; both are purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., MFC, CNF-H1.
[0071] Example 1
[0072] The present embodiment provides a method for preparing an aluminum electrolytic capacitor specially used for a low-temperature resistant detonator detonator, the steps of which are: cutting the positive electrode foil and the negative electrode foil and riveting them respectively with the CP wire; putting a layer of electrolytic paper between the riveted positive electrode foil and the negative electrode foil and winding them to form a core package, injecting electrolyte into the core package, and sealing it in an aluminum shell with colloid particles to obtain a semi-finished capacitor; washing the semi-finished capacitor and then casing it, and sequentially performing primary aging selection, secondary aging selection, observing the appearance, and inspecting it to obtain the capacitor.
[0073] The preparation method of the positive electrode foil comprises the following steps: taking a high-purity aluminum foil for pretreatment, performing a pore-forming and pore-expanding treatment, and air-drying to obtain the positive electrode foil.
[0074] The specific steps of the pretreatment are: immersing the high-purity aluminum foil in the immersion liquid for 15 seconds, then taking it out and air-drying it.
[0075] The impregnation liquid is an acrylic resin aqueous solution, and the mass fraction of the acrylic resin is 1%.
[0076] The specific steps of the pore generation are as follows: the impregnated aluminum foil is used as the anode and the graphite is used as the cathode, and the pore generation solution is placed at a temperature of 85°C and a current density of 0.15A / cm 2 The pore treatment was carried out for 2.5 minutes under the conditions. After completion, the aluminum foil was rinsed with deionized water and air-dried.
[0077] The pore-forming solution is a mixed acid and metal ion aqueous solution, wherein the concentration of the mixed acid is 6 mol / L and the content of the metal ions is 100 ppm.
[0078] The mixed acid is sulfuric acid and hydrochloric acid, and the molar ratio is 4:1.
[0079] The metal ions in the pore-forming solution are iron ions.
[0080] The specific steps of the hole expansion are: the aluminum foil with holes is used as an anode and the graphite is used as a cathode, and they are placed in a hole expansion solution at a temperature of 85°C and a current density of 0.15A / cm 2 The pore expansion treatment was carried out for 6 minutes under the conditions of , and then the aluminum foil was rinsed with deionized water and air-dried.
[0081] The pore-expanding solution is a hydrochloric acid aqueous solution, wherein the concentration of the hydrochloric acid is 1 mol / L.
[0082] The negative electrode foil is a high-purity copper foil.
[0083] The conditions for the primary aging selection are: constant current and constant voltage are used, a constant current of 65 μA is applied, and after the voltage reaches 450 V, constant voltage aging is performed for 4 hours. After the primary aging, the leakage current is tested, and if ≤40 μA, it is qualified and proceeds to the next step.
[0084] The conditions for the secondary aging selection are: pulse and constant voltage methods are used, charging for 120s and discharging for 10s is one pulse, aging for 1.5h at a voltage of 450V, and testing the leakage current after secondary aging. If ≤40μA, it is qualified and proceeds to the next step.
[0085] The preparation method of electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 88°SR, and diluting it with first deionized water to obtain liquid one; taking modified cellulose fiber, mixing it in second deionized water, dispersing it, adding it to liquid one, homogenizing it for 3 hours, making wet paper, pressing and drying the wet paper, and calendering it to obtain electrolytic paper.
[0086] The mass concentration of the absolute dry pulp in the liquid 1 is 2 g / L.
[0087] The added amount of the modified cellulose fiber is 2% of the mass of the absolute dry pulp.
[0088] The mass ratio of the modified cellulose fiber to the second deionized water is 1:150.
[0089] The preparation method of the modified cellulose fiber comprises the following steps: uniformly dispersing the cellulose fiber in a third deionized water, adding a modifier, adjusting the pH of the system to about 10.3, reacting for 4 hours, washing the product with deionized water until it is neutral, and drying to obtain the modified cellulose fiber.
[0090] The cellulose fibers include first cellulose fibers and second cellulose fibers, and the mass ratio of the first cellulose fibers and the second cellulose fibers is 3:1.
[0091] The mass ratio of the cellulose fiber to the third deionized water is 1:200.
[0092] The modifier is 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite, and the mass ratio is 1:10:300.
[0093] The added amount of the modifier is 6 times the mass of the cellulose fiber.
[0094] The wet paper making weight is 25g / m 2 .
[0095] The calendering treatment conditions are: temperature 64°C, pressure 0.18 kgf / cm 2 .
[0096] The thickness of the electrolytic paper is 40 μm.
[0097] The electrolyte includes lithium bis(trifluoromethanesulfonyl)imide and an organic solvent.
[0098] The concentration of the lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 1 mol / L.
[0099] The organic solvent is gamma-butyrolactone, ethylene carbonate, propylene carbonate and methyl acetate.
[0100] The volume fraction of γ-butyrolactone in the organic solvent is 55%.
[0101] The volume ratio of the ethylene carbonate, propylene carbonate and methyl acetate is 1:2:1.
[0102] Example 2
[0103] The difference between this embodiment and embodiment 1 is that the conditions for the primary aging selection are: constant current and constant voltage are used, a constant current of 65 μA is applied, and after the voltage reaches 450 V, constant voltage aging is performed for 3 hours. After the primary aging, the leakage current is tested, and if ≤40 μA, it is qualified and proceeds to the next step.
[0104] The conditions for the secondary aging selection are: pulse and constant voltage methods are used, charging for 120s and discharging for 10s is one pulse, aging for 1.5h at a voltage of 450V, and testing the leakage current after secondary aging. If ≤40μA, it is qualified and proceeds to the next step.
[0105] Example 3
[0106] The difference between this embodiment and embodiment 1 is that the metal ions are ferrous ions.
[0107] Comparative Example 1
[0108] The difference between this comparative example and Example 1 is that the pore-forming solution is a mixed acid aqueous solution, wherein the concentration of the mixed acid is 6 mol / L.
[0109] Comparative Example 2
[0110] The difference between this comparative example and Example 1 is that the mixed acid is replaced by sulfuric acid, and the concentration of sulfuric acid in the pore-forming solution is 6 mol / L.
[0111] Comparative Example 3
[0112] The difference between this comparative example and Example 1 is that the average fiber length of the bleached kraft softwood pulp is 2.9 mm, the average fiber roughness is 17 mg / 100 g, and the average fiber content is 3.9×10 6 roots / g, purchased from Canada Good Voice 400.
[0113] Comparative Example 4
[0114] The difference between this comparative example and Example 1 is that the cellulose fibers are first cellulose fibers.
[0115] Comparative Example 5
[0116] The difference between this comparative example and Example 1 is that the modifiers are sodium bromide and sodium hypochlorite; and the mass ratio of the sodium bromide to the sodium hypochlorite is 1:30.
[0117] Comparative Example 6
[0118] The difference between this comparative example and Example 1 is that the preparation method of the aluminum electrolytic capacitor specially used for low-temperature resistant detonator detonator comprises the following steps: cutting the positive electrode foil and the negative electrode foil and riveting them with the CP wire respectively; putting a layer of electrolytic paper between the riveted positive electrode foil and the negative electrode foil and winding them to form a core bag, injecting electrolyte into the core bag, and sealing it in an aluminum shell with colloid particles to obtain a semi-finished capacitor; cleaning the semi-finished capacitor and then putting it into the casing, and performing aging selection, appearance observation, and inspection in sequence to obtain the capacitor.
[0119] Comparative Example 7
[0120] The difference between this comparative example and Example 1 is that the secondary aging selection conditions are consistent with the primary aging selection conditions.
[0121] Comparative Example 8
[0122] The difference between this comparative example and Example 1 is that the electrolyte is lithium bis(trifluoromethanesulfonyl)imide and high-purity water.
[0123] Comparative Example 9
[0124] The difference between this comparative example and Example 1 is that the organic solvent is ethylene carbonate, propylene carbonate, and methyl acetate.
[0125] Comparative Example 10
[0126] The difference between this comparative example and Example 1 is that the volume ratio of ethylene carbonate, propylene carbonate and methyl acetate is 1:2:5.
[0127] Performance Testing
[0128] The positive foil is applied with 600VF and the negative foil is 3V. The capacitance, internal resistance and 4s leakage current of the aluminum electrolytic capacitor specially used for low-temperature detonator initiators are tested with reference to the method in GB / T 6346.1-2024 "Fixed capacitors for electronic equipment Part 1: General specification".
[0129] High temperature resistance test: Store the capacitor at 85℃ for 10,000 hours, and after returning to room temperature for 1 to 2 hours, test the capacitance of the aluminum electrolytic capacitor for low temperature resistant detonator detonator and calculate the capacitance loss rate. The capacitance loss rate is (initial capacitance - capacitance after test) / initial capacitance × 100%.
[0130] Low temperature resistance test: The capacitor was stored at -40℃ for 10,000 hours, and after returning to room temperature for 1 to 2 hours, the capacitance of the aluminum electrolytic capacitor prepared for low temperature resistant detonator detonator was tested, and the capacitance loss rate was calculated. The results are shown in Table 1.
[0131] Table 1 Measurement results
[0132]
[0133] According to statistics, the aluminum electrolytic capacitors for low-temperature resistant detonator detonators prepared by Examples 1 to 3 of the present invention have excellent electrical properties, a wide operating temperature range, low internal resistance, and small leakage current. No metal ions were added in Comparative Example 1, no hydrochloric acid was added in Comparative Example 2, too large an average content of bleached kraft softwood pulp fibers in Comparative Example 3, no second cellulose fibers were added in Comparative Example 4, no 2,2,6,6-tetramethylpiperidin oxide was added in Comparative Example 5, no secondary aging selection was performed in Comparative Example 6, the secondary aging selection conditions in Comparative Example 7 were consistent with the primary aging selection, the electrolyte in Comparative Example 8 was water, there was no γ-butyrolactone in the organic solvent in Comparative Example 9, and too much methyl acetate was added in Comparative Example 10. The prepared aluminum electrolytic capacitors for low-temperature resistant detonator detonators each had defects. Therefore, the aluminum electrolytic capacitors for low-temperature resistant detonator detonators prepared by the raw materials and methods described in this application have excellent electrical properties, a wide operating temperature range, low internal resistance, and small leakage current.
[0134] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a special aluminum electrolytic capacitor for a low-temperature resistant detonator detonator, characterized in that: The following steps are involved: The positive electrode foil and the negative electrode foil are cut and riveted with the positive guide pin and the negative guide pin; the electrolytic paper is placed between the riveted positive electrode foil and the negative electrode foil and rolled to form a core package, and the electrolyte is injected into the core package, and then the core package is sealed in an aluminum shell with colloid particles to obtain a semi-finished capacitor; the semi-finished capacitor is washed and sleeved, and primary aging selection, secondary aging selection, appearance observation, and inspection are carried out in sequence to obtain the capacitor; The preparation method of the positive electrode foil comprises the following steps: taking a high-purity aluminum foil, performing a pretreatment, performing a pore-forming and pore-expanding treatment, and air-drying to obtain the positive electrode foil; The specific steps of the pore generation are: the impregnated aluminum foil is used as an anode and the graphite is used as a cathode, and is placed in a pore generation solution at a temperature of 80 to 90° C. and a current density of 0.1 to 0.2 A / cm 2 The pore-forming treatment was carried out for 2 to 3 minutes under the conditions. After completion, the aluminum foil was rinsed with deionized water and air-dried. The pore-forming solution is a mixed acid and metal ion aqueous solution. The content of metal ions in the pore-forming solution is 50 to 150 ppm; The metal ions include one or more of ferric ions, ferrous ions, cupric ions, and zinc ions; The preparation method of electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 85-90°SR, diluting it with first deionized water to obtain a first liquid; taking modified cellulose fiber, mixing it in a second deionized water, dispersing it, adding it to the first liquid, homogenizing it for 2-4 hours, making wet paper, pressing and drying the wet paper, and calendering it to obtain electrolytic paper; The average fiber length of the bleached kraft softwood pulp is 2.8-3.2 mm, the average fiber roughness is 18-20 mg / 100 g, and the average fiber content is (2.8-3.0)×10 6 roots / g, viscosity is 18~22CP.
2. The method for preparing a low-temperature resistant aluminum electrolytic capacitor for detonator detonator according to claim 1, characterized in that: The conditions for the primary aging selection are: constant current and constant voltage are used, a constant current of 60 to 70 μA is applied, and after the voltage reaches 440 to 460 V, constant voltage aging is performed for 2 to 6 hours. After the primary aging, the leakage current is tested, and if ≤40 μA, it is qualified and proceeds to the next step.
3. The method for preparing a low-temperature resistant aluminum electrolytic capacitor for detonator detonator according to claim 1, characterized in that: The conditions for the secondary aging selection are: pulse and constant voltage methods are used, charging for 120s and discharging for 10s is one pulse, aging for 1-2h at a voltage of 440-460V, and testing the leakage current after secondary aging. If ≤40μA, it is qualified and proceeds to the next step.
4. The method for preparing a low-temperature resistant aluminum electrolytic capacitor for detonator detonator according to claim 3, characterized in that: The method for preparing medium-density electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 83-87°SR, diluting it with deionized water until the mass concentration of absolute dry pulp in the system is 1.5-2.5 g / L, making wet paper, pressing and drying the wet paper, and then calendering it to obtain medium-density electrolytic paper.
5. The method for preparing a low-temperature resistant aluminum electrolytic capacitor for detonator detonator according to claim 1, characterized in that: The preparation method of the modified cellulose fiber comprises the following steps: uniformly dispersing the cellulose fiber in a third deionized water, adding a modifier, adjusting the pH of the system to be stable between 10 and 10.5, reacting for 3 to 5 hours, washing the product with deionized water until it is neutral, and drying the product.
6. The method for preparing a low-temperature resistant aluminum electrolytic capacitor for detonator detonator according to claim 5, characterized in that: The cellulose fibers include first cellulose fibers and second cellulose fibers.
7. The method for preparing a low-temperature resistant aluminum electrolytic capacitor for detonator detonator according to claim 6, characterized in that: The length of the first cellulose fiber is 0.1-1 nm, and the diameter is 100-1000 nm; the length of the second cellulose fiber is 1-20 μm, and the diameter is 20-80 nm.
8. The method for preparing a low-temperature resistant aluminum electrolytic capacitor for detonator detonator according to claim 1, characterized in that: The electrolyte includes lithium bis(trifluoromethanesulfonyl)imide and an organic solvent.
9. The method for preparing a low-temperature resistant aluminum electrolytic capacitor for detonator detonator according to claim 8, characterized in that: The organic solvent is gamma-butyrolactone, ethylene carbonate, propylene carbonate and methyl acetate.
10. An aluminum electrolytic capacitor prepared by the method for preparing an aluminum electrolytic capacitor specially used for low-temperature resistant detonator initiator according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-voltage and ultralow-impedance aluminum electrolytic capacitor of superior EMI property
CN106910634A
Ultra-low impedance shrinkage chip electrolytic capacitor and preparation method thereof
CN108899208A
Anode aluminum foil for aluminum electrolytic capacitor and preparation method thereof
CN118299186A
Electrolytic capacitor
JP2002043181A
Cited By
Anti-drying wide-temperature-range liquid aluminum electrolytic capacitor and preparation method thereof
CN120914029A